Light-weight Routing Protocol in IoT-based Inter-Device Telecommunication Wireless Environment - Hayoung Oh; Sangsoon Lim (Institute of Advanced Engineering and Science, 2016)
The primary task for IoT-based hyper-connectivity communications lies in the development of direct communications technique among IoT devices in RPL (Routing Protocol for Low-Power and Lossy Networks) environment without the aid from infras such as access points, base stations etc. In a low-power and lossy wireless network, IoT devices and routers cannot keep the original path toward the destination since they have the limited memory, except for a limited number of the default router information.. Different from the previous light-weight routing protocols focusing on the reduction of the control messages, the proposed scheme provides the light-weight IPv6 address auto-configuration, IPv6 neighbor discovery and routing protocol in a IoT capable infra-less wireless networks with the bloom filer and enhanced rank concepts. And for the first time we evaluate our proposed scheme based on the modeling of various probability distributions in the IoT environments with the lossy wireless link. Specifically, the proposed enhanced RPL based light-weight routing protocol improves the robustness with the multi-paths locally established based on the enhanced rank concepts even though lossy wireless links are existed. We showed the improvements of the proposed scheme up to 40% than the RPL based protocol.